New Journalism Ecologies in East and Southern Africa
XXIII, 319 p. 13 illus.
Keywords: This volume presents case studies of news media employing and integrating social media into their news production practices. It links social media use to journalistic practices and news production processes in the digital age of the Global South. Critically, the chapters look at seminal cases of start-up news media whose content is informed by trends in social media, ethical considerations and participatory cultures spurred by the wide use of social media. There has been considerable research looking at the potential of new media technologies, traditional journalism and citizen reporting. The extent to which these new media technologies and ‘citizen journalism’ have morphed or reconfigured traditional journalism practice remains debatable. Currently, there are questions around the limits of social media in journalism practice as the ethical lines continue to become blurred. It is this conundrum of the role of social media in the reconfiguration of the media, news making, production and participatory cultures that requires more investigation. Social media has also turned the logic of the political economy of media production on its head as citizens can now produce, package and distribute news and information with shoestring budgets and in authoritarian regimes with no license of practice. This new political economy means the power that special interest groups used to enjoy is increasingly slipping from their hands as citizens take back the power to appropriate social media journalism to counter hegemonic narratives. Citizens can also perform journalistic roles of investigating and whistleblowing but with a lack off, or limited, regulation. This volume seeks to explore and untangle these issues, and provides an invaluable resource for researchers across the field of journalism, mass media, and communication studies. Trust Matsilele is senior lecturer in the Department of Media and Public Relations, Cape Peninsula University of Science and Technology, South Africa. Shepherd Mpofu is Associate Professor of Media and Communication at UNISA, South Africa. Dumisani Moyo is Executive Dean of Humanities at North West University, South Africa. .